2021
DOI: 10.1038/s41434-021-00219-z
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of retinal ganglion cells in optic nerve injury using cell-selective AAV mediated delivery of SIRT1

Abstract: SIRT1 prevents retinal ganglion cell (RGC) loss in models of optic neuropathy following pharmacologic activation or genetic overexpression. The exact mechanism of loss is not known, prior evidence suggests this is through oxidative stress to either neighboring cells or RGC specifically. We investigated the neuroprotective potential of RGC-selective SIRT1 gene therapy in the optic nerve crush (ONC) model. We hypothesized that AAV-mediated overexpression of SIRT1 in RGCs reduces RGC loss, thereby preserving visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…To increase AAV7m8 transduction efficiency to RGCs and achieve therapeutic effects in these cells, AAV7m8 was further modified to drive transgene expression by an RGC-selective SNCG promotor ( Figure 1 A). In preliminary experiments, we demonstrated the potential of AAV7m8.SNCG.eGFP, which carries SNCG promoter-driven eGFP to transduce RGCs in the mouse retina to a similar degree as in prior studies [ 25 ]. AAV7m8.SNCG.eGFP was injected intravitreally into 4-week-old mice, and the reporter transgene expression in RGCs was analyzed four weeks later ( Figure 1 B).…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…To increase AAV7m8 transduction efficiency to RGCs and achieve therapeutic effects in these cells, AAV7m8 was further modified to drive transgene expression by an RGC-selective SNCG promotor ( Figure 1 A). In preliminary experiments, we demonstrated the potential of AAV7m8.SNCG.eGFP, which carries SNCG promoter-driven eGFP to transduce RGCs in the mouse retina to a similar degree as in prior studies [ 25 ]. AAV7m8.SNCG.eGFP was injected intravitreally into 4-week-old mice, and the reporter transgene expression in RGCs was analyzed four weeks later ( Figure 1 B).…”
Section: Resultssupporting
confidence: 55%
“…The use of the SNCG promoter allowed a highly efficient targeted transfer and translation of the functional transgene cassette into RGCs with greater than 90% cell selectivity. A previous study showed similar RGC-selective expression of eGFP using this construct in a traumatic injury model [ 25 ] although this study did not describe the expression pattern of the therapeutic human SIRT1 transgene. The selection of the SNCG promoter was derived from previous studies showing that the fraction of GCL cells expressing SNCG (45%) matched the estimated fraction of RGCs in the mouse GCL (41–44%), indicating that the SNCG promoter is active in nearly all RGCs [ 31 ].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations